Dual effects of impurity seeding on pedestal turbulence and ELMs in the HL-2A tokamak. (23rd September 2021) - Xiao, G.L.; Zou, X.L.; Zhong, W.L.; Xu, M.; Zhang, Y.P.; Mazon, D.; Dong, C.F.; Dong, J.Q.; Fang, K.R.; Feng, B.B.; Gao, J.M.; Han, M.K.; et al.
Abstract: The control of the edge localized mode (ELM) in tokamaks has been intensively investigated with different techniques. Recently, ELM control with impurity seeding has also raised to be a hot topic. This paper reports the effect of the laser blow-off impurity seeding on the pedestal turbulence and ELMs. It has been found that the seeded impurity could have dual impacts on pedestal instabilities, depending on the quantity of the injected impurity. The impurity enhances the pedestal turbulence and further mitigates the ELMs when its quantity exceeds a lower threshold. Instead, the impurities suppress the pedestal turbulence and suppress ELMs when the quantity of the injected particles reaches a second higher threshold. It has also been observed that the ion toroidal velocity increases due to the impurity seeding while the collision rate is increasing. In addition, the impurities reduce the velocity shear rate by changing the toroidal velocity term rather than by changing the pressure gradient term as observed in ELM mitigation with LHCD. The reduction of the E × B velocity shear rate enhances the pedestal turbulence possibly through the turbulence spectral shift process during ELM mitigation.